Detection of pediatric drug-induced kidney injury signals using a hospital electronic medical record database - Yu, Yuncui; Nie, Xiaolu; Zhao, Yiming; Cao, Wang; Xie, Yuefeng; Peng, Xiaoxia; Wang, Xiaoling (Frontiers in Pharmacology, 2022)
Background: Drug-induced kidney injury (DIKI) is one of the most common complications in clinical practice. Detection signals through post-marketing approaches are of great value in preventing DIKI in pediatric patients. This study aims to propose a quantitative algorithm to detect DIKI signals in children using an electronic health records (EHRs) database. Methods: Twelve years of medical data collected from a constructed data warehouse was analysed, which contained 575,965 records of inpatients from January 1, 2009 to December 31, 2020. Eligible participants included inpatients aged 28 days to 18 years old. A two-stage procedure was adopted to detect DIKI signals: (i) stage 1: the suspected drugs potentially associated with DIKI were screened by calculating the crude incidence of DIKI events and ; (ii) stage 2: the associations between suspected drugs and DIKI were identified in the propensity-score matched retrospective cohorts. Unconditional logistic regression was used to analyze the difference of the incidence of DIKI events as well as to estimate the odds ratio (OR) and 95% confidence interval (CI). Potentially new signals were distinguished from already known associations concerning DIKI by manually reviewing published literature and drug instructions. Results: Nine suspected drugs were initially screened from a total of 652 drugs. Six drugs, including diazepam (OR=1.61, 95%CI: 1.43-1.80), omeprazole (OR=1.35, 95%CI: 1.17-1.54), ondansetron (OR=1.49, 95%CI: 1.36-1.63), methotrexate (OR=1.36, 95%CI: 1.25-1.47), creatine phosphate sodium (OR=1.13, 95%CI: 1.05-1.22), and cytarabine (OR=1.17, 95%CI: 1.06-1.28), were demonstrated to be associated with DIKI as positive signals. The remaining three drugs, including vitamin K1 (OR=1.06, 95%CI: 0.89-1.27), cefamandole (OR=1.07, 95%CI: 0.94-1.21), and ibuprofen (OR=1.01, 95%CI: 0.94-1.09), were found not to be associated with DIKI. Of these, creatine phosphate sodium was considered to be a possible new DIKI signals as it had not been reported in both adults and children previously. Moreover, three other drugs, namely, diazepam, omeprazole, and ondansetron, were shown to be new potential signals in pediatrics. Conclusion: A two-step quantitative procedure to actively explore DIKI signals using real-world data (RWD) was developed. Our findings highlight the potential of EHRs to complement traditional spontaneous reporting systems (SRS) for drug safety signal detection in a pediatric setting.